Education on Utilization of Online Queuing Application Based on Khanza Health Information System for Patients and Families - Masdah, Siti; Putriasti Mayarestya, Nita; Nuruniyah, Nuruniyah; Diana Meilantika, Ayu; Rizky, Ayu (SPEKTA (Jurnal Pengabdian Kepada Masyarakat : Teknologi dan Aplikasi), 2025)
Background: RS Bhayangkara Pontianak faces challenges in managing patient queues due to the high volume of visits and low utilization of online queue applications based on the Khanza Health Management Information System (SIMKES). Contribution: This community service activity aims to improve patients’ and families’ understanding and ability to use online queue applications independently. Method: Through a participatory educational approach, the educational intervention lasted one day and involved 45 participants who had never used the application. Education was provided through short counselling sessions, leaflet distribution, video tutorial screening, and direct simulation of application use. Results: 51.1% of participants were delighted with the educational material, 48.9% with the delivery method, and 60% felt helped by the simulation. Confidence in using the application increased significantly, especially among younger participants. However, older users showed limited progress due to low digital literacy. These results indicate that a participatory educational approach effectively encourages the adoption of digital health tools. Conclusion: The need for ongoing training for patients and staff, the provision of easily accessible self-study materials, and the integration of digital literacy education into routine hospital operations.